Hardware Acceleration for Post-Quantum Cryptography in Resource Constrained Embedded Systems with RISC-V ISEs - Gewehr, Carlos; Moraes, Fernando (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2025: Anais do XXXVIII Concurso de Teses e Dissertações, 2025)
The imminent rise of practical quantum computing threatens well-established cryptography algorithms for secret key exchange in use today, such as Diffie-Hellman and Elliptic Curve (ECC) based schemes. These algorithms are currently being replaced by quantum-safe Crystals-Kyber, also known as ML-KEM. This work aims to explore hardware acceleration through RISC-V Instruction Set Extensions (ISEs) in a low-end 32-bit core in a comprehensive evaluation comprising performance, energy consumption, memory footprint and die area costs, enabling an efficient implementation of a cryptosystem that can withstand attacks from the emergence of quantum computers and is compliant to modern cryptographic standards and algorithm suites. Three different parametrizations of Kyber symmetric primitives are evaluated: the well-known SHA-3 and AES/SHA-2 based versions, as well as a novel parametrization using Ascon. This work also explores ISE-enhanced implementations of algorithms for authenticated encryption (AEAD) and hash functions at the 128 and 256 bit security levels, evaluating improvements due to the use of specialized instructions in each algorithm.